Experimental infection of commercial layers with wild or attenuated Salmonella Gallinarum mutant strains: Anatomic pathology, total blood cell count and serum protein levels - Garcia, K. O. [UNESP]; Berchieri, A. [UNESP]; Santana, A. M. [UNESP]; Alarcon, M. F F [UNESP]; Freitas Neto, O. C. [UNESP]; Fagliari, J. J. [UNESP] (FapUNIFESP (SciELO), 2013)
The aim of the present study was to comparatively evaluate hemogram, blood serum components and anatomopathologic alterations in commercial layers experimentally challenged with an attenuated vaccine candidate strain (SGΔcobSΔcbiA) and other two pathogenic strains (SGΔcobS and SGNalr) of Gallinarum (SG). In total, 280 commercial layers were randomly divided into 4 groups (G1, G2, G3 and G4). At five days of age, birds from groups G1 received approximately 107 colony forming units (CFU) of SGΔcobS; meanwhile birds from group G2 and G3 received the same dose of SGNalr and SGΔcobSΔcbiA, respectively. Birds from G4 were not infected. At 24 hours before (DBI) and 24 hours after (1 DAI), and three (3 DAI), five (5 DAI), seven (7 DAI) ten (10 DAI), and fifteen (15 DAI) days after the infection, 10 birds of each group were humanely killed and blood samples collected to hematological and serum tests. Samples of liver, spleen, thymus, bursa of Fabricius, kidney and heart were also collected for the histological examination. Birds inoculated with SGΔcobS and SGNalr showed similar alterations in hemogram, blood serum components and anatomopathologic exams. On the other hand, the exams of birds inoculated with SGΔcobSΔcbiA strain were similar to those of the uninfected birds. However, changes could be noticed in levels of uric acid and cholesterol during the course of the infection of birds from G3. Decrease in levels of light IgG 3 DAI was also observed in birds from this group. Pyknosis in kidney cells was a microscopic alteration found in birds from G3. Further studies must be done to verify if these alterations will not interfere in the performance of the vaccinate birds with SGΔcobSΔcbiA strain.
Keywords: Acute-phase proteins; Attenuation; Fowl typhoid; Histopathology; Leukogram